Evaluation of analgesic activity of Toxicodendron radicans in animal model using wistar albino rats - V., Marzana K.; Bhat, Nagapati Prabhakar; Nayak, Roopa P.; N., Megha Rani (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Pain forms an integral part of many clinical conditions management is of great importance in every field of medicine. The core of medicine is to preserve and restore patient’s health and to minimize their suffering. Toxicodendron radicans (rhus toxicodendron) is a homoeopathic remedy with anti-inflammatory activity used for various arthritic pain. Rhus toxicodendron is commonly used in skin, mucus membrane affections, pain in joints, tendons, rheumatism in cold season, cellulitis and infection, fever. During the recent exponential rise in the use of alternative medicines and increasing integration into the health service little research has been done on alternative medicine in the context in which it is practiced. Methods: Wistar albino rats were divided into four groups. group 1 received control (normal saline), group 2 received vehicle (alcohol with distilled water in ratio 1:4), and group 3 received standard (diclofenac-10 mg/kg), group 4 and 5 consist of 2 test groups-rhus toxicodendron 30x and 200c respectively. Analgesic activity was assessed using Hot water tail immersion method and Eddy’s hot plate method. Preliminary pilot study was done with 4 doses rhus toxicodendron 6x, 12x, 30x, 200c respectively. Data was analysed by one-way ANOVA followed by Tukey Kramer multiple comparison test. P value <0.05 was considered as significant. Results: In Eddy’s hot plate method, rhus toxicodendron 30 showed increase in paw withdrawal time which was statistically very significant at the end of 1 hr compared to the control group whereas statistically rhus toxicodendron 200 showed extremely significant analgesic property. In hot water tail immersion method rhus toxicodendron 30 showed increase in tail withdrawal time at the end of 1hr compared to the control group which was significant statistically. Conclusions: This study shows that toxicodendron radicans homoeopathic formulations possess significant analgesic property.